Світова практика застосування концепції розводілй влад - Пехник, Алевтина Валентинівна; Козьміних, Альона Віталіївна; Пехник, Алевтина Валентиновна; Козьминіх, Алена Витальевна; Pehnik, А.; Koz'minіh, А. (My University, 2013)
In this article analysis of theory of partition of sovereignty in its historical aspect, taking into account world experience of this conception application is given. Practice of partition of sovereignty application is presented by such countries as the USA, France and Ukraine.
Пехник А. В., Козьміних А. В. Світова практика застосування концепції розводілй влад / А. В. Пехник, А. В. Козьміних // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 174-186.
Keywords: теорія розподілу влади; практика розподілу влади в Україні, США, Франції; історія використання теорії розподілу влад; теория разделения власти; практика разделения власти в Украине, США, Франции; история применения теории разделения власти; theory of separation of powers; the practice of separation of power in Ukraine, the USA, France; history of application of the theory of separation of powers